النظام القانوني لحاضنات الاعمال في الجزائر - بوعافية، حكيم; صالحي ،عبد الرقيب; لحيو ،عبد الكريم (جامعة الوادي, 2024)
تلعب حاضنات الأعمال دورا هاما في دعم وتطوير الأنشطة الناشئة في ولاية الوادي بتقديم مجموعة من الخدمات والدعم. يقدمون أماكن عمل مجهزة بأسعار معقولة للمؤسسات الناشئة، مما يساعدها على تقليل والتركيز على أعمالهم. تقدم بعض الحاضنات أيضًا قروضًا أو استثمارات إلى المشاريع الناشئة. لمساعدتهم على تمويل مشاريعهم، توفر الحاضنات أيضًا الناشئة المشاريع التي تقدم التوجيه والتوجيه من قبل خبراء في مجالات مختلفة مثل تنظيم المشاريع، والتسويق والإدارة المالية. تهدف حاضنة جامعة الوادي إلى دعم وتطوير المشاريع الناشئة، حيث وهو يوفر مجموعة من الخدمات للمؤسسات الناشئة، بما في ذلك أماكن العمل، والمالية وتقديم الدعم والتدريب، ومساعدة المؤسسات الناشئة عن طريق تقديم قروض بدون فوائد. انها زيادة فرص نجاح المؤسسات الناشئة، وخلق فرص عمل جديدة، و يساهم في التنويع. الاقتصاد المحلي، لكنه يواجه أيضًا بعض التحديات من عدم وجود ونقص الوعي المجتمعي بأهمية هذه الحاضنات، والافتقار إلى التمويل خبراء متخصصون في مجال تنظيم المشاريع. Business incubators play an important role in supporting and developing emerging enterprises in the Valley State by providing a range of services and support. They provide equipped workspaces at reasonable prices for emerging enterprises, which helps them reduce costs and focus on their business. Some incubators also provide loans or investments to emerging enterprises. To help them finance their projects, incubators also provide emerging enterprises with guidance and mentoring by experts in various fields such as entrepreneurship, marketing, and financial management. The University of the Valley Incubator aims to support and develop emerging enterprises, as it provides a range of services to emerging enterprises, including work spaces, financial support and training, and helps emerging enterprises by providing interest-free loans. It increases the chances of success of emerging enterprises, creates new job opportunities, and contributes to diversification. The local economy, but also faces some challenges from lack of funding, lack of community awareness of the importance of these incubators, and lack of specialized experts in the field of entrepreneurship
ماستر أعمال